Does Argumentation Change Minds? A Cognitive and Evolutionary Approach - Santibáñez, Cristián (Informal Logic, 2024)
Our intuition is straightforward: yes, argumentation changes minds. But many cognitive and discursive habits suggest otherwise. As the literature in the psychology of reasoning incessantly emphasizes, we hardly change our minds because a predisposed robust confirmation bias (or myside bias) is at work when we argue. To adequately answer the questions of why, how, and if argumentation changes minds, I frame the problem from an evolutionary perspective. I argue argumentative competence changes minds because its ultimate goal is to construct the future, to predict more accurately. This converges with evolutionary analyses of other cognitive skills and cultural inventions. To explain my perspective, I use the distinction between ultimate and proximal goals of a trait.